A Mutated Nme1Cas9 Is a Functional Alternative RNase to Both LwaCas13a and RfxCas13d in the Yeast S. cerevisiae - Zhang, Yadan; Ge, Huanhuan; Marchisio, Mario Andrea (Frontiers in Bioengineering and Biotechnology, 2022)
CRISPR–Cas systems provide powerful biological tools for genetic manipulation and gene expression regulation. Class 2 systems, comprising type II, type V, and type VI, have the significant advantage to require a single effector Cas protein (Cas9, Cas12, and Cas13 respectively) to cleave nucleic acids upon binding the crRNA. Both Cas9 and Cas12 recognize DNA and induce a double-strand break in it. In contrast, Cas13 bind and cleave RNA exclusively. However, some Cas9 homologs have shown RNase activity as well. Here, we harnessed Nme1Cas9, LwaCas13a, and RfxCas13d to carry out gene downregulation in Saccharomyces cerevisiae by triggering mRNA degradation. To avoid potential DNA damage, we mutated Nme1Cas9 into d16ANme1Cas9 that lost the nuclease activity of the RuvC domain but retained the active HNH domain, able to act on the target DNA strand and, therefore, on the corresponding transcript. Our results showed that d16ANme1Cas9 is a functional RNase in vivo, although with moderate activity since it provoked a fluorescence reduction from 21 % to 32 %. Interestingly, d16ANme1Cas9 works in a PAM-independent way nor demands helper PAMmer molecules. LwaCas13a and RfxCas13d appeared substantially unfunctional in S. cerevisiae, though they were shown to perform well in mammalian cells. To the best of our knowledge, this is the first report about the working in vivo of a variant of Nme1Cas9 as an RNase and the issues connected with the usage of Cas13 proteins in S. cerevisiae.